What, Then, Is Liturgy? : Musings and Memoir - Chupungco, Anscar J. (Book collections on Project MUSE., 2010)
"Father Anscar Chupungco fondly recalls his first class as a student at the Pontifical Liturgical Institute in 1965. Professor Salvatore Marsili--famed theologian, liturgist, and cofounder of the institute--entered the lecture hall, and after a prolonged and awkward silence finally asked, "And so, what is liturgy?"" "This seemingly simple question underlies Chupungco's untiring love for liturgy and his lifetime of searching for answers. His is a passion deeply rooted in tradition, which is evident in this volume. Relying on Scripture, patristic writers, and conciliar and postconciliar documents--and with great skill, prudence, and the fundamental virtue of obedience--he carefully examines current liturgical trends that are the subject of fierce debate. At a time when we focus so intently on the debate itself, Chupungco cautions us to remember: "At the end of the day what matters are not personal opinions but what truly contributes to making the prayer of the Church an encounter with the person of Christ. "It is this most sacred encounter that is at the heart of What, Then, Is Liturgy? And it is this encounter that will lead us day by day to the ultimate heavenly liturgy, our eternal and perfect offering of praise to God."--BOOK JACKET.